3030 Symptom profile of chronic rhinosinusitis versus obstructive sleep apnea in a tertiary rhinology clinic. (27th March 2019) - Yong Ji, Keven Seung; Risoli, Thomas J.; Kuchibhatla, Maragatha; Chan, Lyndon; Hachem, Ralph Abi; Jang, David
Abstract : OBJECTIVES/SPECIFIC AIMS: Patients with undiagnosed obstructive sleep apnea (OSA) will often present to an otolaryngologist with symptoms of chronic rhinosinusitis (CRS). Differentiating CRS from OSA may help obviate unnecessary and costly work-up for CRS. This study analyzes symptom profiles of such patients to help identify which require polysomnography. METHODS/STUDY POPULATION: This is a three-year retrospective analysis of adult patients seen in an academic practice with a rhinologic chief complaint. The 22-Item Sinonasal Outcomes Test (SNOT-22) survey, which is a validated patient-reported outcome measure widely adopted for CRS featuring a symptom scale of 1 (least severe) to 5 (most severe), was completed by patients with untreated OSA confirmed on polysomnography without CRS (OSA group) and a control group of CRS patients (CRS group). Results were compared using Chi-square test (categorical) and Wilcoxon rank-sum test (continuous) with Bonferroni correction, and multiple logistic regression. RESULTS/ANTICIPATED RESULTS: 43 patients were included in the OSA group [mean apnea-hypopnea index: 27.9 (SD: 21.2)] and 124 patients were included in the CRS group. The CRS group demonstrated significantly higher scores in nasal (p < 0.001), extra-nasal (p < 0.001) and ear/facial symptom domains (p = 0.001) while the OSA group reported higher psychological (p = 0.028) and sleep symptom domain scores (p = 0.052). As for the cardinal symptoms of CRS, nasal discharge and loss of smell were significantly higher in the CRS group (both p < 0.001), whereas facial pain (p = 0.117) and nasal obstruction (p = 0.198) were not significantly different between the two groups. After adjustment, for every 1-point increase in a patient's score for ear pain, thick nasal discharge and loss of smell or taste, their odds of having CRS increased by a factor of 3.18 [(95% CI 1.61-6.29), p = 0.001], 1.60 [(95% CI 1.22-2.10], p = 0.001] and 1.36 [(95% CI 1.04-1.78), p = 0.025], respectively, compared to having OSA. OSA patients were more likely to choose a sleep-related symptom as a "most important complaint" (MIC) (p < 0.001). Facial pain and nasal obstruction were the most common MIC in the rhinologic domain for OSA patients, whereas thick nasal discharge and post-nasal discharge were the most common MIC for CRS patients. DISCUSSION/SIGNIFICANCE OF IMPACT: For patients presenting with rhinologic symptoms, the SNOT-22 can help identify those with undiagnosed OSA. OSA should be suspected in patients with sleep and psychological dysfunction as their primary complaints without the significant nasal drainage and anosmia that characterizes CRS.